Mineralogical and microstructural evolution of Portland cement paste/argillite interfaces at 70 °C – Considerations for diffusion and porosity properties. (January 2019) - Lalan, Philippines; Dauzères, Alexandre; De Windt, Laurent; Sammaljärvi, Juuso; Bartier, Danièle; Techer, Isabelle; Detilleux, Valéry; Siitari-Kauppi, Marja
Abstract: A Portland cement (CEM I) paste was poured onto an argillite disk in diffusion cells with reservoirs filled by alkaline water and argillite pore water. The system evolution was followed over the course of 415 days. The imposed temperature of 70 °C affected the mineralogy (precipitation of crystallized C-S-H) and mechanical strength of the interface that became brittle over time. The interface consisted of a calcite/tobermorite/C-A-S-H layer, whose thickness increased at a growth rate of 0.3 μm/d. Contrary to calcite crusts that formed in immersion tests or when hardened cement was placed in contact with argillite, this layer had no significant effect on the diffusion properties during the one-year duration of the experiment due to its microporous structure and rather small thickness (100 μm). The argillite mineralogy was altered over 100 μm. In the cement paste, the total porosity decreased because carbonation was enhanced with temperature, which counterbalanced the effect of decalcification over 400 μm.